Optimized design for controlling LED display matrix by an FPGA board - Khalid, MATEUR; Rachid, EL GOURI; Hamad, DAHOU; Laâmari, HLOU (Journal of Advanced Computer Science & Technology, 2014)
The very important objective of the digital designer when using discrete gates for implement a Boolean function is to keep the number of used gates to a minimum and win a memory space without lost the original information. In this sense, the Simplification is very important and could be achieved by a purely algebraic process, but it can be tedious when it arrived to a very large number of variables. In this paper we describe an automat solution based on finite state machine (FSM) for simplify and practically optimize the complex logical functions. This method is programmed and tested on a display system which is based on light emitting diodes (LED) matrix and programmable platform with Field Programmable Gate Array (FPGA). The module is implemented in Spartan 3E family XC3S500E FPGA board. Keywords: Display Board, FPGA, FSM, LED, LED-Driver, Logic Simplification, Multiplex.